2015
DOI: 10.1016/j.mad.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of steroid biosynthesis by retinoid signaling: Implications for aging

Abstract: Retinoids (vitamin A and its derivatives) are critical for a spectrum of developmental and physiological processes, in which steroid hormones also play indispensable roles. The StAR protein predominantly regulates steroid biosynthesis in steroidogenic tissues. We reported that regulation of retinoid, especially atRA and 9-cis RA, responsive StAR transcription is largely mediated by an LXR-RXR/RAR heterodimeric motif in the mouse StAR promoter. Herein we demonstrate that retinoids are capable of enhancing StAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 85 publications
1
30
0
Order By: Relevance
“…RA plays a role in activating RARs and RXRs, steroid thyroid hormone receptor transcription factors. In 2015, it was reported that RA may restore steroidogenesis in epidermal keratinocytes of aged individuals [ 19 ]. Additionally, retinol increases epidermal thickness by upregulation of transcription factors, collagen genes responsible for wound healing, improving extracellular matrix microenvironment, extracellular matrix production, and activating dermal fibroblasts [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…RA plays a role in activating RARs and RXRs, steroid thyroid hormone receptor transcription factors. In 2015, it was reported that RA may restore steroidogenesis in epidermal keratinocytes of aged individuals [ 19 ]. Additionally, retinol increases epidermal thickness by upregulation of transcription factors, collagen genes responsible for wound healing, improving extracellular matrix microenvironment, extracellular matrix production, and activating dermal fibroblasts [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Retinoid-responsive StAR transcription is largely regulated by an RXR/RAR heterodimeric motif in the mouse StAR promoter [ 79 ]. Moreover, retinoid receptors are capable of increasing the expression of the StAR protein [ 80 ], and RXRα interacts directly with GATA-4 [ 81 ]. In the present study, both RORαandGATA-4 were expressed in the goat testis in an age-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The larger the dots, the greater the number of genes that are significantly differentially expressed. mitochondria (Manna et al, 2015). To determine whether IL-6…”
Section: Il-6 Expression Was Upregulated In Facamentioning
confidence: 99%